Походження білорусів. Сучасна історіографія проблеми - Чаквін, І. (Народна творчість та етнографія, 2009)
In the article modern concepts of an origin and an ethnic history of the Byelarussian people are considered. New directions in studying of the given problems and prospect of the further researches are marked.